PENGARUH MODEL PEMBELAJARAN MEANS ENDS ANALYSIS (MEA) BERBANTUAN SOFTWARE BAGATRIX TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Nadia, Riski; Musriandi, Riki; Aryani, Irma; Anzora, Anzora; Rahmi, Rahmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The purpose of this study was to determine the effect of the Means Ends Analysis (MEA) learning model assisted by bagatrix software on the mathematical problem solving abilities of class XI students. The type of research used is quantitative with a one shot case study research design. The population of this study were all students of class XI at SMA Negeri 1 Baitussalam for the 2022/2023 academic year. The sample selection used purposive sampling and XI MIA 1 class was selected as the sample because it met the necessary criteria. Data collection techniques were carried out using tests to determine students' mathematical problem solving abilities and student response questionnaires to determine student responses to the application of the MEA learning model assisted by bagatrix software. The results showed that the mathematical problem solving abilities of class XI students of SMA Negeri 1 Baitussalam were already very good at 26% or equal to 6 people, good 65% or the equivalent of 15 people, and in the sufficient category as much as 9% or the equivalent of 2 people. The results show that there is an influence of the MEA learning model assisted by bagatrix software on students' problem solving abilities